Comparison of anaerobic threshold, oxygen uptake and heart rate between specific table - Zagatto, Alessandro Moura; Papoti, Marcelo [UNESP]; Reis, Ivan Gustavo Masseli dos; Gobatto, Claudio Alexandre (My University, 2012)
The purposes of this study were to: 1) compare the oxygen uptake (VO2) and heart rate (HR) corresponding at anaerobic threshold intensity measured during graded incremental exercise tests (GTX) in table tennis-specific protocol (ST), treadmill (TT), cycle ergometry (CE) and arm crank ergometry (AE); 2) correlate the AnT intensity among ST, TT, CE and AE; verify the use of VO2 and HR at AnT and the AnT intensity for predicting the table tennis performance. Eleven Brazilian table tennis male players of national level (19.4±0.7 years; body mass: 70.8±3.9 kg) participated to the study. The athletes underwent four maximal graded incremental exercise tests performed in ST using a Tibhar RoboPro Plus ball throwing machine and on TT, CE and AE; and also a simulated tournament among players to estimate the table tennis performance ranking. During graded incremental exercise tests, blood samples were collected after each 3-min exercise stage to determine the anaerobic threshold, which corresponded to 3.5 mmol/L fixed blood lactate concentration. VO2 and HR were also measured during GTXs. The AnT corresponded 42.8±5.6 balls.min-1 to ST, 131.9±6.6 W to CE, 64.5±6.1 W to AE and 11.1±0.3 km. h -1 to TT. The VO2 and HR at AnT measured in ST (37.2±1.7 ml. kg-1.min-1 and 182.8±7.2 bpm, respectively) were similar to values obtained in CE (29.8±1.9 ml. kg-1.min-1 and 157.2±7.1 bpm) and TT (36.3±1.0 ml. kg-1.min-1 and 166.0±10.2 bpm), but it was significantly different to AE (18.2±1.1 ml. kg-1.min-1 and 132.7±4.7 bpm). AnT in ST was only significantly correlated with AE (r= .89), while VO2 at AnT in ST was significantly correlated with values measured in CE (r= .92) and TT (r= .81). However, the variables measured during maximal graded incremental exercise tests in ST, CE, AE and TT were not statistically correlated with the table tennis performance ranking analyzed by Spearman correlation test. The results did show that there are differences among the results from table tennis-specific test and from conventional ergometers (i.e., CE, TT and AE); few significant correlations among them; and any parameter did show significant correlation with table tennis performance. These results indicate the importance of using table tennis-specific test to evaluate the anaerobic threshold in table tennis players and that the parameters measured cannot predict the table tennis performance.
Keywords: Table tennis; Aerobic endurance; Table tennis performance; Mechanical ball thrower